Behavior of Geosynthetic Encased Stone – Bagasse Ash as Column in Soft Clay - Balasubramanian Elankumaran, Stalin V. K. (International Journal of Advanced Science and Technology, 2020)
Soft clays are characterized by their low bearing capacity and high compressibility. Stone column is one of the most suitable methods to improve the bearing capacity and reduce the settlement of soft clay. It is difficult to obtain stones of desirable size and gradation owing to their demand in other civil engineering application and high cost. Increasing rate of population and urbanization in developed and developing countries result in large amount of production of waste like bagasse ash. In this investigation, an attempt was made to use the bagasse ash as column material in the place of conventional stone aggregate to improve the soft clay deposit. In this connection the load carrying capacity with and without column, load test were conducted in a model tank on soft clay with one, two and three columns of stone aggregate and ash column for varying geogrid encasement length, number of column and Load to Depth (L/D) ratio. Based on the analysis of load-settlement characteristics of soft clay with one, two and three columns of stone and ash column with and without geogrid encasement in experimental analysis, we inferred that load carrying capacity for any settlement increases with number of columns and l/d ratio for both CSC and bagasse ash as column.